Late Hallstatt/Early La Tene in the Northern Croatia - Potrebica, Hrvoje (Array, 2007)
The transitional period from the Late Hallstatt to the Early La T&egrave ; ; ; ne is not just a question of chronological distinction between the Early and the Late Iron Age. It is more cultural process that in different areas of Europe followed different patterns. We are especially interested in problem of initial exposure of the Late Hallstatt communities to the La T&egrave ; ; ; ne cultural influences and consequent mechanisms of cultural transfer that developed in different areas, which did not necessarily include influx of new population. The aim of this colloquium is to establish diversity of such patterns on examples of several case studies and offer fresh models for interpretation of this process which is crucial for understanding of later prehistory of Europe.